PERAN MATA PELAJARAN KEORGANISASIAN TERHADAP SIKAP KEPEMIMPINAN SISWA MA MU’ALLIMIEN MUHAMMADIYAH LEUWILIANG BOGOR - Khofifah Indah Nurhasanah; Oking Setia Priatna; Abristadevi Abristadevi (Universitas Pahlawan Tuanku Tambusai, 2022)
There is a decrease in leadership attitudes in students so that schools need subjects that support to maintain student leadership attitudes so that they are well maintained and there is no continuous decline in student leadership attitudes. Organizational subjects have a role in student leadership attitudes, namely student responsibility, student discipline, student confidence, and student communicativeness. The author uses descriptive qualitative research methods, the data obtained through interviews, questionnaires, and documentation. The approach used by the researcher is a field research approach, namely the results of the data as research findings, abstracted to obtain complete information on drawing conclusions. This research took place at MA Mu'allimien Muhammadiyah Bogor. Based on the research that has been done, the following results are organizational subjects are sciences that study organizational values ​​and leadership, which include organizational theories, basic theories of leadership, basic theories of management, basic theories of problem solving. In the learning process there are teachers who have certain competencies, enthusiastic students, use organizational book media, use lecture, discussion, and question and answer methods, study materials that have been designed, and evaluate organizational learning subjects by means of UAS, UTS, and other assignments. So that organizational subjects have a role in the leadership attitude of the students of MA Mu'allimien Muhammadiyah Leuwiliang Bogor. This is evidenced from the results of the calculation of the correlation value or R relationship which is equal to 0.557, the coefficient of determination (R square) is 0.311 which implies that the X variable to the Y variable is 31.1%. The results of the data that have been presented show that the significance value obtained is 0.001 which means that the X variable affects the Y variable. Keywords: Organizational Subjects, Attitudes, Student Leadership